Increasing the Creativity of Children with Special Needs through Waste Recycling - Vicky Ananda Burky (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
This study explores the potential of waste recycling programs to promote the creativity of children with special needs. The study is based on a review of qualitative data from parents, teachers, and program leaders who have participated in waste recycling programs with children with special needs. The results suggest that waste recycling programs can have a positive impact on the creativity, social skills, and self-esteem of children with special needs. By using recycled materials, these programs provide a unique and engaging way for children to explore and experiment with different materials and techniques, fostering a sense of creativity and innovation. Additionally, these programs provide opportunities for collaboration and teamwork, which can promote the development of social skills and the formation of positive relationships among program participants. These findings highlight the potential of waste recycling programs to be an effective tool for promoting the well-being and personal growth of children with special needs, and suggest that further research is needed to identify the key components of effective programs.